Ceriscoides glabra (Gardenieae: Rubiaceae), a new species from Kon Chu Rang Nature Reserve, southern Vietnam - Binh, Tran Duc; Quang, Bui Hong; Cuong, Nguyen The; Quynh, Ha Quy; Hoan, Duong Thi; Hai, Do Van; Nguyen, Khang Sinh; Nuraliev, Maxim S. (Phytotaxa, 2022)
Ceriscoides glabra, a new species of the tribe Gardenieae (Rubiaceae), is described and illustrated. The species was discovered in 2017–2018 in Kon Chu Rang Nature Reserve (Gia Lai Province, southern Vietnam), in the vicinity of the locally well-known K50 waterfall, also known as Hang En waterfall. The new species differs from its congeners by the following features: plant entirely glabrous, leaf blade mostly less than 6.5 cm long and less than 4 cm wide, with 3–4 pairs of secondary veins and without domatia, calyx in female flowers glabrous with lobes more than 9 mm long, and corolla lobes in female flowers more than 10 mm long and distinctly longer than wide.